Factors of Fetal Origin in the Regulation of Labor Initiation and Preterm Birth - Yang Pan; Longkun Ding; Lu Gao (Maternal-Fetal Medicine)
Abstract. Preterm birth is the leading cause of mortality and morbidity in newborns and children under 5 years-of-age. In order to improve the survival rate and quality of preterm infants, there is critical need to identify the specific mechanisms underlying the initiation of labor. Pregnancy represents a period of constant interactive dialog between mother and fetus. A disturbance in the pattern of maternal-fetal communication can induce physiological or pathological labor. Although a number of studies have investigated the contributions of maternal factors to the initiation of labor, the concept that fetal organ development and maternal adaptation are coordinated has emerged over recent years, thus emphasizing that factors of fetal origin may serve as hormonal signals for the initiation of labor. In this review, we summarize and discuss several specific mechanisms by which factors of fetal origin may influence parturition during term or preterm labor, including the specific regulation of fetal organs, including the lungs and accessory organs during pregnancy. Future research may focus on the specific pathways by which signals from the fetal lungs and other fetal organs interact with the maternal system to initiate eventual labor.